Grado de satisfacción del usuario según niveles de clima organizacional en el centro de salud San Martín De Porras 2016 - Mantilla Alayo, Rayssa Ximena (2017)
The present investigation is of descriptive correlational type, was carried out in the Health Center San Martin de Porras - Trujillo 2016, in order to establish the relationship between the degree of satisfaction of the internal user and the level of organizational climate. The sample consisted of 30 workers from the Health Center who met the inclusion criteria of the research. For data collection, three instruments were used: The Organizational Climate Scale and the Herzbergian job satisfaction and dissatisfaction scale. The information obtained was processed and analyzed using the Chi square statistical test. Collecting the information, we reached the following conclusions: When the level of organizational climate is higher, the same frequency increases the degree of job satisfaction. The degree of satisfaction of the internal user has a highly significant relationship with the level of organizational climate. (P = 0.0037).